Identification And Analysis Of The Needs For The Development Of Integrated Ipas Learning Management Approach Mindful, Meaningful, Joyful Learning With Ict Multimedia In Elementary Schools Of Tuban Regency - Dumiyati; Djoko Apriono; Agus Wardhono; Novia Hardiyanti; Sri Handayani (Tsaqila | Jurnal Pendidikan dan Teknologi, 2026)
This study identifies and analyses the needs for developing IPAS (Natural and Social Sciences) learning management that integrates the Mindful, Meaningful, and Joyful Learning (MMJ Learning) approach with ICT multimedia in elementary schools in Tuban Regency. Although previous studies have examined ICT integration, school-based mindfulness, and meaningful or joyful learning separately, few have addressed how these three dimensions can be managed together within a single, technology-supported instructional design for primary science; this study addresses that gap. A mixed-methods design was used, combining descriptive quantitative analysis of teacher and student questionnaires with thematic analysis of interviews, observations, and documents across six schools (12 teachers and 60 students). The central finding is a persistent gap between the readiness of ICT facilities and teachers’ pedagogical capacity to integrate them: school facilities are largely adequate, yet teachers’ ability to integrate ICT into learning remains only moderate, and the available teaching tools rarely accommodate the mindful dimension. Students, in turn, strongly prefer visual, interactive, and experiential learning over text. The study’s main contribution is an evidence-based, three-component development framework resources, MMJ-multimedia learning design, and collaboration creativity outcomes that reframes the problem from device provision to learning management. Accordingly, it recommends developing modular ICT multimedia that embeds reflective (mindful), contextual (meaningful), and enjoyable (joyful) activity flows, supported by explicit time-management and collaboration scaffolds.